1970
DOI: 10.24843/spektran.2015.v03.i01.p010
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Sistem Pengadaan Proyek Konstruksi Terhadap Penyerapan Anggaran Pemerintah Kabupaten Badung

Abstract: : The rate of absorption of a government budget, especially on the construction projects, determine whether or not the optimal development of a region. The faster the budget absorption of the construction projects, the faster the perceived benefits. The purpose of the study was to determine the rate of the budget absorption, to find out the factors in the construction project procurement systems that affect the slow budget absorption of the Local Government of the Badung Regency as well as the efforts to minim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…If not properly anticipated, these mistakes will already be implemented, so the contractor bears the risk. This research is in line with research by Sutarja et al, (2020) the cause of delay is caused by owner, planning consultant, supervisory consultant, contractor, and results from the research by Rachid et al (2019) who found the causes of delays, payment problems made and ineffective planning and scheduling of contractors, while the results of this study are compared with previous studies thus the value of the coefficient of other factors on time performance is -0.134 (meaning the effect is negative), P Value on Y is 0.181 < 0.05 (meaning not significant), t-count on Y is 0.913 > T table 1.64 (meaning not significant) then it has no effect on time performance.…”
Section: Hypothesis Testingsupporting
confidence: 93%
See 1 more Smart Citation
“…If not properly anticipated, these mistakes will already be implemented, so the contractor bears the risk. This research is in line with research by Sutarja et al, (2020) the cause of delay is caused by owner, planning consultant, supervisory consultant, contractor, and results from the research by Rachid et al (2019) who found the causes of delays, payment problems made and ineffective planning and scheduling of contractors, while the results of this study are compared with previous studies thus the value of the coefficient of other factors on time performance is -0.134 (meaning the effect is negative), P Value on Y is 0.181 < 0.05 (meaning not significant), t-count on Y is 0.913 > T table 1.64 (meaning not significant) then it has no effect on time performance.…”
Section: Hypothesis Testingsupporting
confidence: 93%
“…So that the work schedule becomes late in time, and costs result in an increase in project costs. And in line with research Sutarja et al (2020) found the cause of delay is caused by owner, planning consultant, supervisory consultant, contractor, non-technical problems of the surrounding community and government and other factors, while research by Buya et al (2022) stated that the main factors of delay in building construction were caused by human resources, financial resources and working methods. The main factor of project delay is also caused by changes in specification / design with a weighting value of 0.1264, and while research by Melyana & Sulistio (2022) which found errors in choosing a construction method with a weight value of 0.0912 need good planning and working methods, and research by Al Amri & Oztemir (2022) found that managerial issues involve delays in payments to contractors.…”
Section: Hypothesis Testingmentioning
confidence: 66%
“…To answer the question is the sole objective of this research. The public construction project in Indonesia mainly consists of two phases: the procurement phase and contract execution phase (Astadi, Sutarja, & Nadiasa, 2015). The latter is the phase the government difficult to control because there are plentiful peculiarities involved in the stage (Zidane & Andersen, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the regulation on housing procurement 4 offers three different methods other than build mechanism. Those are swap, grant, and buy-directly-from-developer (Ashaf & Hidayat, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The procurement practices of goods/services and the increasing procurement performance of goods/services will be followed by the increased utilization of eprocurement technology, and is expected to accelerate and increase the realization of state and regional expenditures. But in fact in some research such as Arif (2012); Sukadi (2012); Juliani & Sholihin (2014); Astadi, Sutarja & Nadiasa (2015); Malahayati, Islahudin, & Basri (2015) revealed that the practice of procurement of goods/services is the main factor causing delays in budget absorption. Sirup.lkpp.go.id (2016) stated that East Java Province is the province that has the second largest procurement of goods/services in Indonesia in 2016 with total procurement of 11,905 packages and total ceiling of Rp4,793,120 million, which is done through E-procurement system.…”
Section: Introductionmentioning
confidence: 99%